Condensation on Surfaces With Biphilic Topography: Experiment and Modeling - Alizadeh-Birjandi, Elaheh; Alshehri, Ali; Kavehpour, H. Pirouz (Frontiers in Mechanical Engineering, 2019)
Optimization of the efficiency of the condensers via different surface engineering techniques is a subject of interest due to its wide range of application in thermal management for aerospace vehicles, power generation systems, and etc., which will further result in considerable savings in annual investments and operating costs by millions of dollars. However, the current technologies are lacking either the necessary condensation enhancements or cost-effective, large-scale fabrication method. In this work, we present a new surface topography to enhance drop-wise condensation at low manufacturing costs. These surfaces consist of macro-scale hydrophobic patterns on hydrophilic structures. Due to their high wettability contrast, the biphilic surfaces enhance drop-wise condensation with long-term functionality, and more importantly, they can be easily manufactured in large-scale using conventional methods as no nano- or micro-features are needed.